From Values to Value: Unpacking the Impact of Work Ethics, Discipline, Compensation, and Fairness on Employee Satisfaction - Putri, Alya Fahriyah Natasa; Suyana, Hilma; Zain, Efendy (Human Capital and Organizations, 2025)
This study aims to determine the effect of work ethics, work discipline, work compensation, and organizational fairness on job satisfaction at Biro Klasifikasi Indonesia (Persero) in North Jakarta. The sampling technique used was simple random sampling. Data were collected via a questionnaire. The data analysis methods used were multiple regression analysis and partial test (t). The results of the study showed that work ethics did not have a significant effect on job satisfaction; work discipline had a positive and significant impact; work compensation had a positive and significant effect; and organizational justice had a positive and significant impact. The managerial implications are that management of PT. Biro Klasifikasi Indonesia (Persero) needs to emphasize the importance of improving work discipline, providing fair and appropriate compensation, and creating a transparent and equitable organizational justice system, as these three factors have been proven to affect employee job satisfaction significantly. The managerial implications of this research indicate that PT. Biro Klasifikasi Indonesia (Persero) should prioritize strengthening employee discipline through explicit rules and consistent supervision, ensuring fair, performance-based compensation, and maintaining transparency in organizational justice to foster trust and employee satisfaction.